Analisis Bentuk-Bentuk Bullying dalam Film Rumah untuk Alie di Netflix - Evi Lia Fauziah; Koesworo Setiawan; Agustini Agustini (Institut Nalanda, 2026)
Bullying is a social phenomenon that frequently occurs in everyday life and is often portrayed in media as a reflection of power imbalance This study aims to analyze the forms of bullying represented in the film Rumah untuk Alie on Netflix. This research employs a qualitative descriptive approach using a representation analysis method. Data were collected through observation of selected scenes depicting bullying behaviors in the film. The findings reveal that bullying is represented in various forms, including physical, verbal, emotional, and social exclusion. These forms are portrayed through interactions between characters in both family and social environments, illustrating how bullying occurs in different contexts. The results indicate that bullying in the film is not presented as a simple act, but rather as a complex social phenomenon involving emotional impact and unequal power relations. This study implies that film, as a medium, plays an important role in shaping audience understanding of bullying, particularly in recognizing that bullying can occur not only physically but also through subtle social and emotional actions.